Properties and local environment of p-type dopants and photoluminescent rare-earths implanted into zon single-crystals - Rita, Elisabete Maria Casa Nova Correia, 1976- (2008)
Tese de doutoramento em Física, apresentada à Universidade de Lisboa através da Faculdade de Ciências, 2008